Phase distortion correction in dual-comb ranging system. (2nd June 2017) - Li, Yao; Shi, Junkai; Wang, Yanqing; Ji, Rongyi; Liu, Deming; Zhou, Weihu
Abstract: We systematically discussed the principle of the dual-comb ranging system and built a theoretical model. To correct the phase distortion caused by femtosecond frequency comb noise, a correction approach is proposed and numerical simulations are conducted subsequently. In the simulations, the performance of the method under noise of repetition rate and offset frequency is analyzed respectively. The results indicate that ranging accuracy can be effectively improved by the method. It is verified by the experiments.